Analysis Implementation the Implementation of the Merdeka Curriculum in Strengthening Character Education Besed on Qur’anic Vision in Elementary Schools - Liya Fauzul Muna; Zulela MS (Jurnal Inovasi dan Riset Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum based on a Qur’anic vision in elementary schools, focusing on the coherence between curriculum planning, instructional practices, and learning assessment. The Merdeka Curriculum provides flexibility for schools to design contextual and student-centered learning, allowing the integration of spiritual and character values aligned with the school’s vision. A qualitative descriptive approach was employed, with data collected through classroom observations, interviews, and document analysis of the School Operational Curriculum (KOSP), instructional planning documents, and learning practices. The findings indicate that elementary schools with a Qur’anic vision have implemented the Merdeka Curriculum effectively in terms of curriculum planning and the cultivation of religious character values. Qur’anic values are reflected in the school’s vision and mission, school culture, and daily learning activities. However, the implementation of learning strategies that promote critical and creative thinking, as well as the use of authentic assessment, remains limited. Teachers tend to rely on existing teaching modules without sufficient contextual adaptation, and assessment practices still emphasize learning outcomes rather than learning processes. This study concludes that the implementation of the Merdeka Curriculum based on a Qur’anic vision contributes positively to the development of students’ religious character. Nevertheless, strengthening pedagogical innovation, independent teaching module development, and authentic assessment practices is necessary to optimize the objectives of the Merdeka Curriculum in elementary education.